2022
DOI: 10.1186/s13054-022-04066-1
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care practice and moral distress during COVID-19 pandemic (PEOpLE-C19 study): a national, cross-sectional study in intensive care units in the Czech Republic

Abstract: Background Providing palliative care at the end of life (EOL) in intensive care units (ICUs) seems to be modified during the COVID-19 pandemic with potential burden of moral distress to health care providers (HCPs). We seek to assess the practice of EOL care during the COVID-19 pandemic in ICUs in the Czech Republic focusing on the level of moral distress and its possible modifiable factors. Methods Between 16 June 2021 and 16 September 2021, a na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Spirituality has been identified as an important competency in palliative care in this and earlier studies as also in competency frameworks. 7,10,11,44,45 Due to demographic changes, nurses in clinical practice are increasingly confronted with vulnerable patients who have difficulty expressing their wishes and autonomy. 46 Ideally, a collaborative approach between physicians and nurses, together with, active engagement with patients and their families, is essential for making end-of-life decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spirituality has been identified as an important competency in palliative care in this and earlier studies as also in competency frameworks. 7,10,11,44,45 Due to demographic changes, nurses in clinical practice are increasingly confronted with vulnerable patients who have difficulty expressing their wishes and autonomy. 46 Ideally, a collaborative approach between physicians and nurses, together with, active engagement with patients and their families, is essential for making end-of-life decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Spirituality has been identified as an important competency in palliative care in this and earlier studies as also in competency frameworks. 7 , 10 , 11 , 44 , 45 …”
Section: Discussionmentioning
confidence: 99%
“…Such a strategy allows patient management to be focused on care deemed appropriate and in case of ineffectiveness, to rapidly initiate palliative symptom-oriented care. Furthermore, a recent study showed that perception of inappropriate care was a major risk factor for psychological distress among healthcare providers [31]. Early LTE discussion might help in reducing psychological distress by allowing a better understanding of a well-established therapeutic plan and should thus be investigated in further large randomized studies.…”
Section: Discussionmentioning
confidence: 99%
“…The 2020 National Physician Burnout and Suicide Report showed a 44% rate of burnout among ICU physicians [ 151 ]. The COVID-19 pandemic has increased this rate not only due to dying patients [ 152 ] but also to additional physical and psychological demands with a poor recognition of their work [ 153 , 154 ]. We are at a watershed moment for caregivers and proffering “resilience” as the solution to the burn-out crisis is no longer acceptable [ 155 ].…”
Section: Main Textmentioning
confidence: 99%